2019
DOI: 10.9734/ejmp/2019/v28i430143
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Activity of Essential Oil of Cymbopogon citratus against Oral Microflora Associated with Dental Plaque

Abstract: Aims: Dental biofilms are complex, multi-species microorganism communities that inhabit the oral cavity in the form of dental plaque which causes dental caries and periodontal diseases. The present study aims to explore the potential of Lemon Grass Essential Oil (LGEO) extracted from Cymbopogon citratus as antimicrobial and antibiofilm agent against the microorganisms responsible for dental plaque. Study Design: Observational and comparison study. Place and Duration of Study: Research centre, Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…39 Furthermore, it was shown that lemongrass essential oil has remarkable antimicrobial and antibiofilm activities against the dental plaque bacteria. 40 The oral cavity harbors over 700 different species of bacteria and is described as one of the most intricate ecosystem. Though the majority of them are considered as commensally, some of them are responsible for oral infections ranging from tooth decay to periodontal diseases and gingiva related infections.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, it was shown that lemongrass essential oil has remarkable antimicrobial and antibiofilm activities against the dental plaque bacteria. 40 The oral cavity harbors over 700 different species of bacteria and is described as one of the most intricate ecosystem. Though the majority of them are considered as commensally, some of them are responsible for oral infections ranging from tooth decay to periodontal diseases and gingiva related infections.…”
Section: Discussionmentioning
confidence: 99%
“…Minyak atsiri sereh dapur mengandung beberapa senyawa kimia, yaitu sitral, mycrene, genariol, citronellol dan α-oxobisabolene (Oladeji et al 2019). Kandungan minyak atsiri sereh dapur (Cymbopogon citratus) memiliki kemampuan untuk menekan pertumbuhan jamur (Ella et al 2013) dan bakteri (Ambade & Bhadbhade 2015), anti serangga, dan anti kanker (Fitri et al 2019). Beberapa teknologi pengambilan minyak atsiri dari sereh dapur adalah menggunakan penyulingan uap-air (Zaituni et al 2016), distilasi uap, dan air dengan pemanas microwave (Feriyanto et al 2013), dan ekstraksi dengan menggunakan pelarut (metanol, aseton, dan nheksana) (Ariyani et al 2008).…”
Section: Masyarakatunclassified
“…Lemongrass, Cymbopogon citratus (D.C.) Stapf, belonging to the Poaceae family, is an aromatic plant cultivated for the commercial production of essential oil, of which the majority of constituents are generally the citral monoterpenes (isomeric mixture of neral and geranial types) and the myrceno [11]. In Dentistry, the essential oil of Cymbopogon citratus has been shown to have antibacterial properties against Staphylococcus spp., Streptococcus mutans [12] and antifungal properties against several Candida species [12][13][14][15][16]. The antimicrobial properties of the essential oil of Cymbopogon citratus can be attributed to two main components: alpha-citral (geranial) and beta-citral (neral), aromatic compounds responsible for the citric characteristic of the oil [17].…”
Section: Introductionmentioning
confidence: 99%